Analysis of Internet of Things Based Smart Home Systems for Electricity Consumption Efficiency (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2025)
The IoT technology has opened up new horizons in household energy management through smart home systems. Smart home systems are based on the integration of electronic appliances with sensors and actuators, which provide automated and remote control of domestic devices. This article assesses IoT-based smart home systems as a tool for enhancing electricity consumption efficiency in residential domains. The research uses a literature-based approach complemented by prototype development using current sensors, motion sensors, and internet-connected microcontroller modules to collect real-time data about the usage of electrical energy to recognize the patterns of energy consumption among household appliances. A comparative analysis between normal operating conditions and those enabled by smart home automation is carried out. Results show that IoT-based smart homes lower electricity consumption by controlling device operation according to real usage conditions such as turning off idle devices, adjusting lighting levels based on human presence, and allowing remote control of appliances. These results prove that IoT-based smart home systems can be effectively used for reducing household electricity demand in compliance with energy sustainability efforts within digitally connected residential environments.